Penentu pendapatan asli daerah Kabupaten Lembata - Lenny, Lenny (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Regional Original Income is one of the additions to the value of regional assets obtained from receipts of Regional Levies, Regional Taxes, Separated Regional Assets Management Results, and Other Legitimate Regional Original Income. Regional Regulation No. 6 of 2020 states that the Lembata Regency Regional Revenue Agency functions as an executor in the field of Regional Revenue. The purpose of this research is to look at the level of contributions from local taxes, regional levies, the results of separated regional wealth management, and other legitimate local revenue which greatly affects the size of the Lembata Regency Regional Revenue for the 2016 to 2020 fiscal year period. Research design The research used is descriptive research with secondary data originating from the Regional Budget (APBD) of Lembata Regency. The method used is descriptive quantitative analysis. The first position is occupied by other legitimate local revenue for the years 2016 to 2019, but for 2020 it is no longer overtaken by regional levies, while the third and fourth positions are occupied by regional taxes and regional wealth management. which is separated by regional levies and other local revenue is the largest source of regional income, while the third and fourth positions are occupied by regional taxes and the results of separated wealth management.